Effect of supplementation of seaweed by-products based formulations on haematological and serum metabolites profile of growing crossbred calves - Munde, Vitthal Kundlikrao (Indian Journal of Animal Nutrition, 2018)
ABSTRACT This experiment was conducted to study the effect of supplementation of two seaweed byproducts based formulations on haematology and serum metabolite profile of growing crossbred calves. Two seaweed byproducts based formulations namely SWF-1 and SWF-2 were prepared. SWF-1 contained Kapaphycus alvarezi (thrashed weed), Gracilaria salicornia (washed weed) and Kapaphycus water extract at a ratio of 45:45:10, while SWF-2 comprised of Kapaphycus alvarezi (thrashed weed), Gracilaria salicornia (washed weed) and Turbinaria conoides at a ratio of 2:2:1. Thirty five growing cross bred male calves (BW 108.8 to 218.4 kg; average 161.13 kg and 10-15 months of age) were randomly distributed into 5 groups of 7 each. Diets of the calves of control (T0) group contained no seaweed byproducts, whereas, concentrate mixture of experimental calves were supplemented with SWF-1 at 1.5% (T1) and 3.0% (T2), and SWF-2 at 1.5% (T3) and 3.0% (T4), respectively. Blood was collected from all the animals on d 0, 90 and 180 of experimental period. Feed consumption was similar among the groups. Concentration of haemoglobin was higher (P<0.001) in SWF supplemented groups. However, a tendency of increased RBC count was observed only in T4. Supplementation of SWF increased (P<0.001) the relative abundance of lymphocytes with a concomitant decrease (P<0.01) in neutrophil resulting in increased (P<0.01) L:N. Serum concentration of total protein was lower (P<0.001) in T0 as compared to other groups, whereas highest value was observed in T3. Serum concentration of globulin was lower (P<0.001) in T0 as compared to other groups, whereas no difference was observed among the four SWF supplemented groups. Supplementation ofÂ Â seaweed by-products based formulation showed potentials to improve erythropoiesis, cellular immunity and the ability of crossbred calves to combat stress.